Comparative effectiveness of different biochars and conventional organic materials on growth, photosynthesis and cadmium accumulation in cereals. (July 2019) - Azhar, Muhammad; Zia ur Rehman, Muhammad; Ali, Shafaqat; Qayyum, Muhammad Farooq; Naeem, Asif; Ayub, Muhammad Ashar; Anwar ul Haq, Muhammad; Iqbal, Akhtar; Rizwan, Muhammad
Abstract: Although biochar and conventional organic materials have been widely studied for lowering cadmium (Cd) uptake by plants but information regarding their comparative effectiveness is lacking. In this study, biochars from different feedstocks viz . rice husk biochar (RHB), cotton sticks biochar (CSB) and wheat straw biochar (WSB) were compared with conventional organic materials viz. farm manure (FM), poultry manure (PM) and press mud (PrMd) for their effectiveness to promote plant growth and to reduce Cd uptake by wheat and rice plants grown rotationally in a Cd-spiked (50 mg kg −1 ) soil. Each amendment was applied at the rate of 2% (w/w) in three replicates. Results showed that the application of amendments improved the soil properties and plant growth, by retaining Cd in the soil and restricting its uptake by plants. The amendments decreased the ammonium bicarbonate diethylene penta acetic acid extractable soil Cd, and improved soil organic carbon (SOC) and cation exchange capacity (CEC) as compared to only Cd-contaminated soil. The highest SOC content of 2.68 and 1.68% and CEC of 8.77 and 9.39 cmolc kg −1 were found in RHB treated post-wheat and post-rice soil, respectively. Amendments treated soil showed lower concentrations of bioavailable Cd and the maximum reduction was recorded in RHB and PrMd amended soil. Similarly, bioaccumulation of Cd was decreased with the application of all amendments; the maximum decrease was recorded in RHB and PrMd treated soil. Our results suggested that RHB and PrMd could be used for reducing the bioaccumulation of Cd in cereal grains in alkaline soils. Highlights: Rice husk biochar (RHB) and press mud (PrMd) were more effective in increasing growth and biomass of cereals. RHB and PrMd were highly efficient in decreasing cadmium (Cd) concentration in grains of cereals. RHB and PrMd were more effective in decreasing bioavailable soil Cd.